Synthesis and X‐ray Crystal Structures of β‐Ketoiminate Complexes. Issue 21 (24th September 2018) - Steiniger, Phillip; Dittrich, Dennis; Scheiper, Christoph; John, Christoph; Wölper, Christoph; Schulz, Stephan
Abstract : Heteroleptic zinc complexes containing side‐arm donor‐functionalized tridentate β‐ketoiminate ligands were obtained from metalation reactions of β‐ketoimines L1/2/3 Do1/2/3/4 H [L1 = (OC(Me)C(H)C(Me)NCH2 CH2 Do), L2 = (OC(Me)C(H)C(Me)NCH2 CH2 CH2 Do), L3 = (OC(OMe)C(H)C(Me)NCH2 CH2 Do); Do1 = NMe2, Do2 = NEt2 ; Do3 = Pyr, Do4 = OMe] with equimolar amounts of Zn[N(SiMe3 )2 ]2 [L1 Do1 ZnN(SiMe3 )2 (1 ), L1 Do2 ZnN(SiMe3 )2 (2 )] and ZnEt2 [L1 Do3 ZnEt (3 ), L2 Do3 ZnEt (4 ), L3 Do1 ZnEt (5 ), L3 Do4 ZnEt (6 )]. Analogous reactions of AlMe3 and Cp*MMe3 with L1 Do1/2 H yielded homoleptic aluminum [L1 Do1 AlMe2 (7 ), L1 Do2 AlMe2 (8 ), L2 Do1 AlMe2 (9 )], titanium [L1 Do2 Ti(Me2 )Cp* (10 )] and zirconium complexes [L1 Do2 Zr(Me2 )Cp* (11 )]. In addition, 7 reacts with an ethereal HCl solution with methane elimination and formation of L1 Do1 Al(Cl)Me (12 ) and L1 Do1 AlCl2 (13 ), whereas the reaction with one and two equivalents of 2, 6‐dimethylphenol yielded L1 Do1 Al(Me)O‐2, 6‐Me2 C6 H3 (14 ) and L1 Do1 Al(O‐2, 6‐Me2 C6 H3 )2 (15 ). The complexes were characterized by elemental analysis, 1 H, 13 C NMR, and IR spectroscopy and single‐crystal X‐ray analysis (2, 4, 7, 10, 12 –14 ). Abstract :